Amelioration of Ductular Reaction by Stem Cell Derived Extracellular Vesicles in MDR2 Knockout Mice via Lethal‐7 microRNA. Issue 6 (12th April 2019) - McDaniel, Kelly; Wu, Nan; Zhou, Tianhao; Huang, Li; Sato, Keisaku; Venter, Julie; Ceci, Ludovica; Chen, Demeng; Ramos‐Lorenzo, Sugeily; Invernizzi, Pietro; Bernuzzi, Francesca; Wu, Chaodong; et al.
Abstract : Cholangiopathies are diseases that affect cholangiocytes, the cells lining the biliary tract. Liver stem cells (LSCs) are able to differentiate into all cells of the liver and possibly influence the surrounding liver tissue by secretion of signaling molecules. One way in which cells can interact is through secretion of extracellular vesicles (EVs), which are small membrane‐bound vesicles that contain proteins, microRNAs (miRNAs), and cytokines. We evaluated the contents of liver stem cell–derived EVs (LSCEVs), compared their miRNA contents to those of EVs isolated from hepatocytes, and evaluated the downstream targets of these miRNAs. We finally evaluated the crosstalk among LSCs, cholangiocytes, and human hepatic stellate cells (HSCs). We showed that LSCEVs were able to reduce ductular reaction and biliary fibrosis in multidrug resistance protein 2 (MDR2) ‐/‐ mice. Additionally, we showed that cholangiocyte growth was reduced and HSCs were deactivated in LSCEV‐treated mice. Evaluation of LSCEV contents compared with EVs derived from hepatocytes showed a large increase in the miRNA, lethal‐7 (let‐7). Further evaluation of let‐7 in MDR2 ‐/‐ mice and human primary sclerosing cholangitis samples showed reduced levels of let‐7 compared with controls. In liver tissues and isolated cholangiocytes, downstream targets of let‐7 (identified by ingenuity pathway analysis), Lin28a (Lin28 homolog A), Lin28b (Lin28 homolog B), IL‐13 (interleukin 13), NR1H4 (nuclear receptor subfamily 1 group H member 4) and NF‐κB (nuclear factor kappa B), are elevated in MDR2 ‐/‐ mice, but treatment with LSCEVs reduced levels of these mediators of ductular reaction and biliary fibrosis through the inhibition of NF‐κB and IL‐13 signaling pathways. Evaluation of crosstalk using cholangiocyte supernatants from LSCEV‐treated cells on cultured HSCs showed that HSCs had reduced levels of fibrosis and increased senescence. Conclusion: Our studies indicate that LSCEVs could be a possible treatment for cholangiopathies or could be used for target validation for future therapies.